Update on Hypertension Guidelines: A Literature Review - Andika, Gede Agus; Graharti, Risti (CV. Jasa Sukses Abadi, 2025)
Hypertension is one of the major worldwide health problems, with its prevalence continuing to increase year by year. This condition is known as the “silent killer” because it often does not cause specific symptoms, but is closely related to increased morbidity and mortality due to cardiovascular and non-cardiovascular complications. Various epidemiological studies show that hypertension contributes to high rates of coronary heart disease, stroke, kidney failure, and premature death. Recent literature also confirms that risk factors for hypertension include unhealthy lifestyles, high-salt diets, obesity, stress, and genetic predisposition. The diagnosis of hypertension requires accurate blood pressure measurement using standard protocols, either through examinations at healthcare facilities or self-monitoring at home. Various international guidelines, such as ACC/AHA, ESC/ESH, and national guidelines such as PERKI, emphasize the importance of early detection and blood pressure control with specific targets. Hypertension management strategies include non-pharmacological approach such as lifestyle modifications, as well as pharmacological approach using evidence-based antihypertension medications, such as diuretics, ACE inhibitors, ARBs, CCBs, and beta blockers. This literature concludes that hypertension management must be comprehensive, integrated, and sustained to prevent complications. These efforts does not only depend on medical interventions, but also involve patient education, routine monitoring, and health system support to reduce the burden of hypertension in the future.